2013
DOI: 10.15560/9.3.610
|View full text |Cite
|
Sign up to set email alerts
|

First record of two molossid bats (Chiroptera: Molossidae) from Piauí state and distributional review for Brazil

Abstract: The Family Molossidae has a cosmopolitan distribution; it is common in urban areas as well as in agricultural and forested environments. In Brazil, the group comprises seven genera with 25 species. In spite of the representative number of taxa, Molossidae is insufficiently documented in biological inventories. Thus, there is a gap in knowledge about the actual distribution of most species. Here we present new records of tow molossids, Cynomops planirostris and Neoplatymops mattogrossensis, for the state of Pia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…Neoplatymops mattogrossensis had already been found roosting in horizontal and vertical slits in rocks in the Caatinga (Willig 1985b;Novaes et al 2013a) and in the Atlantic Forest (Avilla et al 2001). These authors found that roosts ranged from 0.5 to 5 m above ground level.…”
Section: Natural History Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoplatymops mattogrossensis had already been found roosting in horizontal and vertical slits in rocks in the Caatinga (Willig 1985b;Novaes et al 2013a) and in the Atlantic Forest (Avilla et al 2001). These authors found that roosts ranged from 0.5 to 5 m above ground level.…”
Section: Natural History Notesmentioning
confidence: 99%
“…With the intensification of research, these numbers have grown for bats and other taxa, with new occurrence records and undescribed species emerging (Gregorin and Ditchfield 2005;Gregorin et al 2006;Taddei and Lim 2010;Moratelli et al 2011;Novaes et al 2013a). Although several studies have focused on Caatinga bats (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The specimen is an adult male, with a forearm length of 34.13 mm and weight of 13 g ( Figure 2). The identification was done following the characteristics provided by Rocha et al 2010;Novaes et al 2013). However, Bernard et al (2011a) recognized that the record of this species should be removed from the list of recorded species for the state of Pará due to an error in record keeping for that state.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…The voucher specimens (USNM 531145, USNM 556087) are deposited at the Smithsonian Institution National Museum of Natural History in Washington, DC, USA. These records have not been taken into account by subsequent studies (e.g., Eger 2008;Bernard et al 2011a;Novaes et al 2013), mainly because the article written by Mok and Lacey (1980) was published in the printed version of the journal Acta Amazonica (Portuguese edition), hindering its wider distribution.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…In Brazil, the species has been recorded in the following states (Reis et al, 2013;Santos et al, 2015): Espírito Santo (Ruschi, 1951), Mato Grosso (Pine et al, 1970), São Paulo (Vizotto and Taddei, 1976), Pernambuco (Mares et al, 1981), Distrito Federal (Sá, 1998), Mato Grosso do Sul (Pulchério-Leite et al, 1998), Minas Gerais (Pedro and Taddei 1998), Goiás (Rodrigues et al, 2002), Paraná (Miretzki, 2003), Bahia (Faria et al, 2006), Ceará (Fabián, 2008), Sergipe (Rocha et al, 2010), Paraíba (Feijó and Langguth, 2011), Piauí (Novaes et al, 2013), Amapá (Silva et al, 2013), Roraima (Capaverde-Junior et al, 2014), and Tocantins (Lapenta and Bueno, 2015).…”
Section: Introductionmentioning
confidence: 99%